PERAN PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT IV DALAM MENINGKATKAN KOMPETENSI KEPEMIMPINAN OPERASIONAL - Mardiningsih, Heni (Balai Diklat Keagamaan Surabaya, 2019)
The researcher made preliminary observations to participants, leaders and organizers as well as somepeople who said that the implementation of Level IV Leadership Education and Training was merely anadministrative requirement for echelon IV structural officials who had or would occupy that position. Thepurpose of this study was to find out and analyze the role of Level IV Leadership Education and Training inimproving operational leadership competencies at the Religious Education and Training Center in Surabaya,East Java Province. The method in this research uses descriptive study method approach quality f whichdescribes the data obtained through interviews that are matched with the results of observation anddocumentation. The role of Level IV Leadership Education and Training can be maximal in the formation ofoperational leadership competencies if the calling of participants is in accordance with the stipulatedrequirements, there is intensive and continuous coordination between the organizers of education andtraining with leaders as supervisors, mentors and coaches. guiding change projects, resource persons haveteaching competency certificates Education and leadership training from State Administration institutions,participants focus more on the implementation of change projects than carrying out the functions of theiragency activities, involving resource persons in evaluating participant evaluations at the end of educationand training activities and evaluating and monitoring project changes in the short, medium and long term.